2013
DOI: 10.1105/tpc.113.112227
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Proteomic and Phosphoproteomic Analyses of Successive Stages of Maize Leaf Development

Abstract: We performed large-scale, quantitative analyses of the maize (Zea mays) leaf proteome and phosphoproteome at four developmental stages. Exploiting the developmental gradient of maize leaves, we analyzed protein and phosphoprotein abundance as maize leaves transition from proliferative cell division to differentiation to cell expansion and compared these developing zones to one another and the mature leaf blade. Comparison of the proteomes and phosphoproteomes suggests a key role for posttranslational regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 50 publications
7
97
1
3
Order By: Relevance
“…As expected from its constitutive RNA expression, MS32 was found in both Stage 8 and 10 anthers and was highly abundant in pollen (Table 1). MS32 is a widely expressed protein detected in leaves (Facette et al, 2013) and transcripts are found in multiple organs ( Fig. S13; https://mpss.danforthcenter.org/ dbs/index.php?SITE=maize_RNAseq).…”
Section: Distinct Protein Expression Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected from its constitutive RNA expression, MS32 was found in both Stage 8 and 10 anthers and was highly abundant in pollen (Table 1). MS32 is a widely expressed protein detected in leaves (Facette et al, 2013) and transcripts are found in multiple organs ( Fig. S13; https://mpss.danforthcenter.org/ dbs/index.php?SITE=maize_RNAseq).…”
Section: Distinct Protein Expression Patternsmentioning
confidence: 99%
“…The total counts of RNA-seq reads in each gene model are normalized to 10 million reads (TP10M) (Zhai et al, 2015). The relative spectral abundance of each protein analyzed by HPLC-MS/MS was normalized as described by Facette et al (2013). RNA-seq data are from W23 fertile anthers (Zhai et al, 2015).…”
Section: Impact Of Tp Defects On Small Rna Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of CESAs has attracted much attention because of the recent development in phosphoproteomic studies and genetic manipulation of CESAs. Phosphoproteomic studies in Arabidopsis and maize discovered that CESA proteins including CESA1, CESA3, and CESA5 are phosphorylated in conserved residues of the hypervariable region at the N-terminus (Nuhse et al, 2004;Facette et al, 2013). The role of phosphorylation of CESA1 was tested by complementing the rsw1 mutant with mutated forms of CESA1 that prevent or mimic phosphorylation.…”
Section: Regulation At the Post-transcriptional Levelmentioning
confidence: 99%
“…This technique allowed for the identification of more than 12,000 proteins in a maize leaf developmental time-course experiment (Facette et al, 2013) and a similar number of proteins isolated from developing maize seeds (Walley et al, 2013). These studies provided novel insights into protein accumulation patterns in these maize organs during development, which are instrumental for the better understanding of these biological systems.…”
mentioning
confidence: 99%